(untitled) (Northern International Medical College Journal, 2016)
Background : Malnutrition is a serious public health problem that has been linked to increase risk of morbidity and mortality. Child malnutrition causes 27% of child deaths in developing countries in 2015. Objective : To estimate the nutritional status of under five children of a selected slum in Dhaka city. Methodology : This was a descriptive cross sectional study and conducted among 100 under 5 children purposively selected at Agargaon slum in Dhaka city during January-2015 to July-2015. Anthropometric measurements were taken by using standard methods. Those were weight, height, MUAC. Information regarding age of children was taken from patients birth certificates or hospital records. Nutritional status was estimated by calculating Z-score, weight for age, height for age, weight for height and mid upper arm circumference. Data were analyzed using SPSS version 16. Results : Mean age of the study population was 32.95 months. Male was 52% and female was 48%. Regarding Anthropometric assessment according to weight for height Z-score, 39% were wasted moderately and 13% were severely wasted and height for age Z-score, showed 47% of children were stunted moderately and 14% children were severely stunted. According to weight for age Zscore, 46% of children were moderately underweight and 16% children were severely underweight. According to MUAC classification 43% of children were in border line and 16% were malnutrition. Conclusions : Overall, nutritional status of the under 5 child of slum of Agargaon were not satisfactory. Northern International Medical College Journal Vol.7(2) Jan 2016: 143-145